Short-Term Outcome of Cardiac Surgeries in a Tertiary Care Hospital at the Eastern Part of Nepal - Sharma, Praman; Yadav, Lokesh; Shahbaz, Ahmad; Sharma, Jyotindra; Nepal, Rajesh; Khanal, Sunil Babu; Agrawal, Subhadra; Kattel, Vivek (Journal of Nobel Medical College, 2021)
Background: Cardiac surgical procedures like coronary artery bypass graft surgery and aortic or mitral valve replacements are commonly performed worldwide. In the developing world, Cardio-Thoracic and Vascular Surgery are not adequately accessible except in a few major cities. We established the department to fill that gap at a tertiary center in the eastern part of Nepal. The main objective of the study was to evaluate the short-term outcome of all major cardiac surgeries. Materials and Methods: This is a retrospective study including all cardiac surgery cases operated over 18 months of the establishment. Demographics, various cardiac diseases, co-morbidities, pre-specified peri-operative, and postoperative outcomes were noted in pre-structured questionnaires. The ethical clearance was taken from the hospital ethical committee. Results: There were 67 major cardiac surgery cases performed. Among those 50.7% and 49.3% were males and females respectively with a median age of 50 years. The most common etiology was coronary artery disease (43.28%) followed by rheumatic heart disease (28.35%) and congenital heart diseases (23.88%). The mean cardiopulmonary bypass and aortic cross-clamp times were 93 min and 58 min respectively. The mean intensive care unit and hospital stays were 1.9 and 5.87 days respectively. One (1.5%) patient underwent reexploration and 6(8.9%) patients developed acute kidney injury. Peri-operative survival was 100% whereas the first and third-month survivals were 97% and 95% respectively. Conclusion: Major cardiac surgeries are feasible and safe in newly established cardiac surgery department with acceptable short-term morbidity and mortality.